Global Trends in Information Systems and Software Applications 4th International Conference, ObCom 2011, Vellore, TN, India, December 9-11, 2011. Proceedings, Part II - Krishna, P. Venkata; Babu, M. Rajasekhara; Ariwa, Ezendu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This 2-Volume-Set, CCIS 0269-CCIS 0270, constitutes the refereed proceedings of the International Conference on Global Trends in Computing and Communication (CCIS 0269) and the International Conference on Global Trends in Information Systems and Software Applications (CCIS 0270), ObCom 2011, held in Vellore, India, in December 2011. The 173 full papers presented together with a keynote paper and invited papers were carefully reviewed and selected from 842 submissions. The conference addresses issues associated with computing, communication and information. Its aim is to increase exponentially the participants' awareness of the current and future direction in the domains and to create a platform between researchers, leading industry developers and end users to interrelate.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Database Management